Diseño de una máquina tapadora para envases con cuajo (2017)
The project is based on the need of the company CuajoCol S.A.S. in optimizing the capping time of plastic containers with liquid rennet; that for many years the form manual has been made. The purpose of the capper machine is to improve the performance, quality and process carried out in the company. The design implements an automatic machine to cover the containers, which are first filled by a dosing machine and by means of a conveyor belt for the last one to be covered. The capper machine has the function of sealing the containers with a threaded lid, a measure that expels the sections of the dosing machine, and that respond to the flow of the containers without altering the production time.